2018
DOI: 10.1007/s00221-018-5291-6
|View full text |Cite
|
Sign up to set email alerts
|

You are measuring the decision to be fast, not inattention: the Sustained Attention to Response Task does not measure sustained attention

Abstract: The Sustained Attention to Response Task (SART) has been widely used in psychological literature as a measure of vigilance (the ability to sustain attention over a prolonged period of time). This task uses a Go/No-Go paradigm and requires the participants to repetitively respond to the stimuli as quickly and as accurately as possible. Previous literature indicates that performance in SART is subjected to a "speed-accuracy trade-off" (SATO) resulting from strategy choices and from the failures of controlling mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…The interpretation of these results, however, are hard to interpret for several reasons: (1) RT is the primary behavioral measure (see limits to this approach in the introduction). Moreover, the "go/no-go" detection task used is associated with pronounced criterion effects (e.g., Dang, Figueroa, & Helton, 2018;Doneva & De Fockert, 2014;Helton, Head, & Russell, 2011;Helton, Weil, Middlemiss, & Sawers, 2010), and the authors themselves conclude that they are unable to distinguish whether their results are due to changes in sensitivity or criterion (p. 2026). (2) In the targetpresent trials-75% of trials-of Experiment 2, in which the significant RT feature validity effect was found, detection accuracy was near chance-76.9%.…”
Section: Discussionmentioning
confidence: 96%
“…The interpretation of these results, however, are hard to interpret for several reasons: (1) RT is the primary behavioral measure (see limits to this approach in the introduction). Moreover, the "go/no-go" detection task used is associated with pronounced criterion effects (e.g., Dang, Figueroa, & Helton, 2018;Doneva & De Fockert, 2014;Helton, Head, & Russell, 2011;Helton, Weil, Middlemiss, & Sawers, 2010), and the authors themselves conclude that they are unable to distinguish whether their results are due to changes in sensitivity or criterion (p. 2026). (2) In the targetpresent trials-75% of trials-of Experiment 2, in which the significant RT feature validity effect was found, detection accuracy was near chance-76.9%.…”
Section: Discussionmentioning
confidence: 96%
“…According to the literature on the SART, deliberate control is beneficial for performance on no-go trials. Deliberate control can be employed to sustain attention to the task (e.g., [75]), but also to support a controlled response strategy [76][77][78]. Therefore, the reason why sticky thought was associated with lower performance compared to neutral/non-sticky thought may be because this mode of thought was associated with a lower level of deliberate control.…”
Section: Correlates and Insights For The Stickiness Dimension Of Thoughtmentioning
confidence: 99%
“…The SART shows temporal decline in performance, which Robertson et al (1997) attributed to increasing mindlessness. By contrast, Helton and colleagues (e.g., Dang, Figueroa, & Helton, 2018) have argued that performance change on the SART reflects motor control processes, including speed–accuracy trade-off, rather than any loss of awareness of external stimuli. However, if such strategic factors can be controlled, the task may support further investigation of possible temporal changes in reactive control.…”
Section: Discussionmentioning
confidence: 94%